Widely tunable photonic bandgap and lasing emission in enantiomorphic cholesteric liquid crystal templates. Issue 13 (22nd March 2017) - Lin, Jia-De; Lin, Hong-Lin; Lin, Hsin-Yu; Wei, Guan-Jhong; Chuang, Yu-Chou; Chen, Lin-Jer; Huang, Shuan-Yu; Huang, Chia-Yi; Mo, Ting-Shan; Lee, Chia-Rong
Abstract : Widely tunable reflection and lasing emission in a dye-doped nematic liquid crystal refilled gradient-pitched enantiomorphic cholesteric liquid crystal polymer template. Abstract : Dye-doped nematic liquid crystal refilled gradient-pitched enantiomorphic cholesteric liquid crystal polymer templates are demonstrated. The enantiomorphic device has high reflectivity and wide spectral tunability throughout the entire visible region. This device can also provide low threshold lasing emission with both right- and left-circular polarizations from the blue to the red region.